Religiusitas Wajib Pajak dan Sosialisasi Perpajakan pada Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah - Eka Budi, Putu Wahyu; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p08, 2023)
The aim of this research is to test empirically the religiosity of the taxpayer, and the socialization of taxation has an effect on the taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs) at KPP Pratama East Denpasar. The population used was 6,124 taxpayers, which included individual taxpayers for the MSME sector and corporate taxpayers for the MSME sector, with a sample of 50 individual taxpayers for the MSME sector and 50 corporate taxpayers for the MSME sector. The sampling technique uses a purposive sampling technique which is a sample collection technique based on predetermined criteria. The data analysis technique uses multiple linear regression analysis techniques. The results showed that taxpayer religiosity and tax socialization had a positive effect on MSME taxpayer compliance at KPP Pratama East Denpasar. Keywords: Taxpayer Religiosity; Tax Socialization; Taxpayer Compliance.